Adhesive
By controlling the volume ratio of the magnetic powder and the number average molecular weight of the bisphenol F-type resin in the adhesive of the coil component, the problem of excessive viscosity of the adhesive is solved, and the maintenance of magnetic permeability and the improvement of manufacturing simplicity are achieved.
Patent Information
- Application Number
- CN202411011936.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the adhesive used in the coil component increases the magnetic permeability while being too high in viscosity, which makes it difficult to deal with during coating, affecting the simplicity of manufacturing.
Using an adhesive containing bisphenol F-type resin, curing agent, and magnetic powder, the volume ratio of the magnetic powder is controlled below 35vol%, and the number average molecular weight of the bisphenol F-type resin is controlled from 312g/mol to 360g/mol. between.
It realizes that while ensuring magnetic permeability, the viscosity of the adhesive is reduced, the manufacturing process is simplified, and the processing simplicity of the adhesive is improved.
Smart Images

Figure CN119432285A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to adhesives. Background Art
[0002] The coil component described in Patent Document 1 includes a core body. The core body includes a winding core portion and two flange portions. The winding core portion is in the shape of a quadrangular prism. The two flange portions are connected to both sides of the winding core portion. Each flange portion extends outward from the winding core portion in a direction perpendicular to the central axis of the winding core portion. The material of the core body is a magnetic body. In addition, the coil component includes a top plate. The top plate is in the shape of a roughly rectangular plate. The top plate is connected to the core body by bridging the two flange portions. The coil component includes an adhesive. The adhesive is between the top plate and the core body. Then, the adhesive bonds the top plate and the core body to each other. In addition, the adhesive contains magnetic powder.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2021-190633 Summary of the invention
[0006] The adhesive used in the coil component described in Patent Document 1 contains magnetic powder, and thus has a higher magnetic permeability than when it does not contain magnetic powder. On the other hand, the greater the content of magnetic powder in the adhesive, the higher the viscosity of the adhesive tends to be. If the viscosity of the adhesive is too high, for example, when the adhesive is applied to the top plate using a clamp, phenomena such as adhesive stringing will occur between the clamp and the top plate. That is, due to the increased viscosity of the adhesive, it is difficult to handle the adhesive during application. Therefore, an adhesive is required that ensures sufficient magnetic permeability and is easy to handle during manufacturing.
[0007] In order to solve the above-mentioned problems, the present invention is an adhesive, which is an adhesive containing bisphenol F type resin, a curing agent for the above-mentioned bisphenol F type resin, and magnetic powder, the volume ratio of the above-mentioned magnetic powder to the above-mentioned adhesive is less than 35 vol%, and the number average molecular weight of the above-mentioned bisphenol F type resin is 312g / mol~360g / mol.
[0008] According to the above configuration, a sufficient value of magnetic permeability as an adhesive is ensured, and handling during production is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a three-dimensional diagram of the coil component.
[0010] Figure 2 This is an exploded perspective view of the coil component.
[0011] Figure 3 This is a schematic diagram of the structure of the adhesive before curing.
[0012] Figure 4 It is a graph showing the test results of wire breakage time.
[0013] Figure 5 It is a graph showing the test results of wire breakage time.
[0014] Explanation of symbols
[0015] 10…Coil components
[0016] 10C…Drum core
[0017] 10F…Top plate
[0018] 11…Core
[0019] 20…Flange
[0020] 30…External electrode
[0021] 41…First Wire
[0022] 42…Second wire
[0023] 50…Adhesive
[0024] 51…Bisphenol F resin
[0025] 52…Magnetic powder
[0026] 53…Curing agent
[0027] 54…Curing accelerator
[0028] 55…Silane coupling agent
[0029] 56…Dispersant DETAILED DESCRIPTION
[0030] Hereinafter, an embodiment of a coil component including an adhesive is described with reference to the accompanying drawings. It should be noted that, for ease of understanding, the accompanying drawings sometimes enlarge components. The dimensional ratio of the components sometimes differs from the actual dimensional ratio or the dimensional ratio in other drawings.
[0031] <About coil parts>
[0032] like Figure 1 As shown, the coil component 10 includes a drum-shaped core body 10C as a first core body and a top plate 10F as a second core body.
[0033] The drum-shaped core 10C has a winding core portion 11. The winding core portion 11 is a quadrangular prism having a central axis 11C. The cross section of the winding core portion 11 perpendicular to the central axis 11C is a rectangle. It should be noted that the "rectangle" mentioned here only needs to have four sides and be a rectangle as a whole, and also includes a shape in which the corners of the rectangle are chamfered. The material of the winding core portion 11 is, for example, alumina, Ni-Zn ferrite, synthetic resin, and a mixture thereof. In the present embodiment, the material of the winding core portion 11 is Ni-Zn ferrite, which is a kind of magnetic material.
[0034] Here, a specific axis orthogonal to the central axis 11C of the winding core 11 is set as the first axis X. In the present embodiment, when viewed in the direction along the central axis 11C, the first axis X is parallel to the two short sides of the winding core 11. In addition, an axis orthogonal to both the first axis X and the central axis 11C is set as the second axis Y. In the present embodiment, when viewed in the direction along the central axis 11C, the second axis Y is parallel to the two long sides of the winding core 11. In addition, an axis parallel to the central axis 11C is set as the third axis Z. Moreover, one of the directions along the first axis X is set as the first positive direction X1, and the direction opposite to the first positive direction X1 is set as the first negative direction X2. Similarly, one of the directions along the second axis Y is set as the second positive direction Y1, and the direction opposite to the second positive direction Y1 is set as the second negative direction Y2. In addition, one of the directions along the third axis Z is set as the third positive direction Z1, and the direction opposite to the third positive direction Z1 is set as the third negative direction Z2.
[0035] like Figure 1 As shown, the drum-shaped core 10C has two flange portions 20 connected to the two ends of the winding core 11 along the direction of the central axis 11C. Specifically, the two flange portions 20 are a first flange portion 21 and a second flange portion 22. The first flange portion 21 is connected to the end of the third positive direction Z1 of the winding core 11, that is, the first end. The first flange portion 21 is a flat, roughly square plate. The thickness direction of the first flange portion 21 is along the direction of the third axis Z. When viewed in the direction along the third axis Z, the sides of the first flange portion 21 are roughly parallel to the sides of the winding core 11. In addition, the first flange portion 21 extends outward relative to the outer surface of the winding core 11 in the direction along the first axis X and the direction along the second axis Y. That is, when viewed in the direction along the third axis Z, the first flange portion 21 extends over a full 360-degree circumference relative to the outer surface of the winding core 11.
[0036] The first flange portion 21 has a first recessed portion 21A. The first recessed portion 21A is recessed relative to the end surface of the first flange portion 21 in the first positive direction X1. The first recessed portion 21A is located at the center of the first flange portion 21 in the direction along the second axis Y. The first recessed portion 21A is open on both sides of the first flange portion 21 in the direction along the third axis Z. As a result, the end surface of the first flange portion 21 on the first positive direction X1 side is divided into two parts via the first recessed portion 21A.
[0037] The second flange portion 22 is connected to the end portion on the third negative direction Z2 side of the winding core portion 11, that is, the second end. The second flange portion 22 is symmetrical with the first flange portion 21. That is, the second flange portion 22 is roughly square. The second flange portion 22 extends outward relative to the outer surface of the winding core portion 11 in the direction along the first axis X and the direction along the second axis Y. That is, when viewed in the direction along the third axis Z, the second flange portion 22 extends over the entire 360-degree circumference relative to the outer surface of the winding core portion 11. The second flange portion 22 has a second recess 22A that is the same as the first recess 21A of the first flange portion 21. The material of the first flange portion 21 and the second flange portion 22 is the same Ni-Zn ferrite as the winding core portion 11. That is, the drum-shaped core 10C is made of a magnetic material. In addition, the first flange portion 21 and the second flange portion 22 are integrally molded with the winding core portion 11.
[0038] The top plate 10F is a flat rectangular plate. The thickness direction of the top plate 10F is along the first axis X. The long side of the top plate 10F is parallel to the third axis Z. The short side of the top plate 10F is parallel to the second axis Y. The top plate 10F is located on the first negative direction X2 side relative to the drum-shaped core 10C. Moreover, the top plate 10F is connected to the surface of the first flange portion 21 facing the first negative direction X2 side and the surface of the second flange portion 22 facing the first negative direction X2 side. That is, the top plate 10F is mounted between the first flange portion 21 and the second flange portion 22 and connected to the drum-shaped core 10C. The material of the top plate 10F is the same material as that of the winding core 11. That is, the top plate 10F is a Ni-Zn ferrite as a kind of magnetic material. The top plate 10F forms a closed magnetic circuit together with the drum-shaped core 10C. In the present embodiment, a top plate 10F on which the wires are not directly wound and a flange portion 20 on which the wires are not wound in a drum-shaped core 10C described later are also regarded as the core or a part of the core.
[0039] The coil component 10 is provided with an adhesive 50. The adhesive 50 is disposed between the drum-shaped core 10C and the top plate 10F. That is, the adhesive 50 bonds the drum-shaped core 10C and the top plate 10F. In addition, in the present embodiment, the drum-shaped core 10C and the top plate 10F are in direct contact with the adhesive 50. In other words, the top plate 10F is connected to the two flange portions 20 via the adhesive 50. It should be noted that the details of the adhesive 50 will be described later.
[0040] The coil component 10 includes four external electrodes 30. Specifically, the coil component 10 includes a first electrode 31, a second electrode 32, a third electrode 33, and a fourth electrode 34. The first electrode 31 is located on the end surface of the outer surface of the first flange portion 21 on the first positive direction X1 side. In addition, the first electrode 31 is located on the second positive direction Y1 side relative to the central axis 11C of the outer surface of the first flange portion 21. Specifically, the first electrode 31 is located on the second positive direction Y1 side relative to the first recess 21A.
[0041] The second electrode 32 is located on the end surface on the first positive direction X1 side of the outer surface of the first flange portion 21. In addition, the second electrode 32 is located on the second negative direction Y2 side relative to the central axis 11C of the outer surface of the first flange portion 21. Specifically, the second electrode 32 is located on the second negative direction Y2 side relative to the first recess 21A.
[0042] The third electrode 33 is located on the end surface on the first positive direction X1 side of the outer surface of the second flange portion 22. In addition, the third electrode 33 is located on the second positive direction Y1 side relative to the central axis 11C of the outer surface of the second flange portion 22. Specifically, the third electrode 33 is located on the second positive direction Y1 side relative to the second recess 22A.
[0043] The fourth electrode 34 is located on the end surface on the first positive direction X1 side of the outer surface of the second flange portion 22. In addition, the fourth electrode 34 is located on the second negative direction Y2 side relative to the central axis 11C of the outer surface of the second flange portion 22. Specifically, the fourth electrode 34 is located on the second negative direction Y2 side relative to the second recess 22A.
[0044] Although not shown in the figure, the external electrode 30 has a metal layer and a plating layer. The material of the metal layer is silver. The metal layer is formed on the outer surface of the first flange portion 21 and the second flange portion 22. The plating layer is composed of three layers. The plating layer is sequentially stacked with copper, nickel, and tin on the surface of the metal layer. It should be noted that the end face on the first positive direction X1 side of the coil component 10 is the mounting surface opposite to the substrate when the coil component 10 is mounted on the substrate.
[0045] like Figure 1 As shown, the coil component 10 includes a first wire 41 and a second wire 42. The first wire 41 and the second wire 42 are wound around the winding core 11 of the drum-shaped core 10C.
[0046] Although not shown in the figure, the first wire 41 has a copper wire and an insulating film. The insulating film covers the outer surface of the copper wire. The first wire 41 is substantially circular in a cross section perpendicular to the direction in which the first wire 41 extends. The second wire 42 has the same structure as the first wire 41. That is, the second wire 42 has a copper wire and an insulating film. Figure 1 In FIG. 1 , the first wire 41 is represented by being colored by dots.
[0047] The first end 41A of the first wire 41 is connected to the first electrode 31. The second end 41B of the first wire 41 is connected to the third electrode 33. The first end 41A and the second end 41B are connected to the corresponding external electrodes 30 by heat pressing.
[0048] Furthermore, the first wire rod 41 is wound around the winding core 11 so as to advance clockwise from the first wire end 41A side to the second wire end 41B side when viewed in the third negative direction Z2.
[0049] The first end 42A of the second wire 42 is connected to the second electrode 32. The second end 42B of the second wire 42 is connected to the fourth electrode 34. The first end 42A and the second end 42B are connected to the corresponding electrodes by heat pressing.
[0050] In addition, the second wire 42 is wound around the winding core 11 in a manner that moves clockwise from the first wire end 42A side to the second wire end 42B side when viewed in the third negative direction Z2. That is, the second wire 42 is wound in the same direction as the first wire 41. Moreover, the second wire 42 is wound around the winding core 11 from the outside relative to the first wire 41.
[0051] <About Adhesive>
[0052] like Figure 2 As shown, the adhesive 50 covers the entire surface of the first flange portion 21 facing the first negative direction X2. Moreover, the adhesive 50 connects the first flange portion 21 and the top plate 10F without a gap. Similarly, the adhesive 50 covers the entire surface of the second flange portion 22 facing the first negative direction X2. The adhesive 50 connects the second flange portion 22 and the top plate 10F without a gap. That is, the top plate 10F is connected to the two flange portions 20.
[0053] like Figure 3 As shown, the adhesive 50 contains bisphenol F type resin 51, magnetic powder 52, curing agent 53, curing accelerator 54, silane coupling agent 55 and dispersant 56. It should be noted that Figure 3 The adhesive 50 shown in the figure shows the state before curing. Figure 3 In FIG. 1 , only a part of the magnetic powder 52 , the curing agent 53 , and the curing accelerator 54 are denoted by reference numerals.
[0054] Specifically, the adhesive 50 is manufactured as follows. First, the bisphenol F resin 51, the curing agent 53, the curing accelerator 54, the silane coupling agent 55, the dispersant 56, and the magnetic powder 52 are mixed at a rotation speed of 30 rpm for 5 minutes using a mixer (model: HIVIS MIX (registered trademark) 2P-03 (manufactured by PRIMIX)). Then, a disperser (model: EXAKT 80E (manufactured by NagaseScreen Printing Research Co., Ltd.)) is used to mix at a gap of 6 μm and 230 rpm to manufacture the adhesive 50 before curing.
[0055] In this embodiment, the bisphenol F resin 51 is a bisphenol F epoxy resin. Specifically, the bisphenol F resin 51 is CAS No. 9003-36-5. In this embodiment, both monomers and polymers are collectively referred to as bisphenol F resin 51.
[0056] The number average molecular weight of bisphenol F type resin 51 is 312 g / mol. It should be noted that the number average molecular weight of bisphenol F type resin 51 only needs to be 312 g / mol to 360 g / mol. It should be noted that the number average molecular weight can be measured using GPC (Model: HLC-8120GPC (manufactured by Tosoh Techno-System Inc.)). It should be noted that GPC refers to Gel Permeation Chromatography. In the measurement using this device, the column temperature is 40°C. In addition, in the measurement, tetrahydrofuran is used as a solvent. The flow rate of the solution containing the solvent is 1.0 ml / min. In addition, the standard sample is monodisperse polystyrene.
[0057] In the present embodiment, the volume ratio of the bisphenol F resin 51 to the adhesive 50 is 54.5 vol%. It should be noted that a more preferred volume ratio of the bisphenol F resin 51 to the adhesive 50 is 54.4 vol% to 68.7 vol%. It should be noted that the “volume ratio to the adhesive 50” is a ratio of the volume to the total volume of the adhesive 50 before curing expressed as a percentage.
[0058] The magnetic powder 52 is nickel powder in the present embodiment. Specifically, the magnetic powder 52 is CAS No. 7440-02-0. The magnetic powder 52 includes particles having a particle size of 0.1 μm to 3.0 μm. The volume ratio of the magnetic powder 52 to the adhesive 50 is 35 vol% or less. In the present embodiment, the volume ratio of the magnetic powder 52 to the adhesive 50 is 35 vol%. It should be noted that the volume ratio of the magnetic powder 52 in the adhesive 50 only needs to be 35 vol% or less, and is preferably 20 vol% or more.
[0059] In the particle size distribution of the magnetic powder 52, the median particle size (D50) is 0.8 μm to 2.5 μm. It should be noted that the median particle size (D50) of the magnetic powder 52 is calculated, for example, as follows. First, the magnetic powder 52 is sampled using a scanning electron microscope to obtain a particle size distribution. Next, in the particle size distribution, the frequency of the particle size is accumulated from the minimum particle size to the maximum particle size. The particle size when the cumulative value is 50% is set as the median particle size (D50).
[0060] The curing agent 53 is a curing agent of the bisphenol F type resin 51. In the present embodiment, the curing agent 53 is dicyandiamide. Specifically, the curing agent 53 is CAS No. 461-58-5. The volume ratio of the curing agent 53 to the adhesive 50 is 4.36 vol%. It should be noted that the more preferred volume ratio of the curing agent 53 to the adhesive 50 is 4.36 vol% to 5.49 vol%.
[0061] The curing accelerator 54 is a curing accelerator for the bisphenol F type resin 51. In the present embodiment, the curing accelerator 54 is an amine adduct. Specifically, the curing accelerator 54 is CAS No. 134091-75-1. The volume ratio of the curing accelerator 54 to the adhesive 50 is 2.73 vol%. It should be noted that a more preferred volume ratio of the curing accelerator 54 to the adhesive 50 is 2.72 vol% to 3.43 vol%.
[0062] The dispersant 56 is used to disperse the magnetic powder 52 in the adhesive 50. In the present embodiment, the dispersant 56 is a modified carboxyl polymer. Specifically, it is a modified carboxyl polymer having an acid value of 55 mgKOH / g. The volume ratio of the dispersant 56 to the adhesive 50 is 3.1 vol%. It should be noted that the more preferred volume ratio of the dispersant 56 to the adhesive 50 is 2.18 vol% to 3.13 vol%.
[0063] In this embodiment, the silane coupling agent 55 is glycidoxypropyltrimethoxysilane. Specifically, the silane coupling agent 55 is CAS No. 253-83-8. The volume ratio of the silane coupling agent 55 to the adhesive 50 is 0.3 vol%. It should be noted that a more preferred volume ratio of the silane coupling agent 55 to the adhesive 50 is 0.24 vol% to 0.35 vol%.
[0064] <About the characteristics of adhesive>
[0065] The glass transition temperature of the cured adhesive 50 is above 125°C. The glass transition temperature of the adhesive 50 is measured as follows. First, after mixing bisphenol F type resin 51, curing agent 53, curing accelerator 54, silane coupling agent 55, dispersant 56, and magnetic powder 52, they are fired for 3 hours in an atmosphere of 150°C to prepare a cured bonding test piece. The dimensions of the bonding test piece are 20 mm in length, 10 mm in width, and 1.5 mm in thickness. Then, the two short sides of the above-mentioned bonding test piece are fixed to a viscoelasticity measuring device (model: DMS7100 (manufactured by Hitachi High-Tech Corporation)) to measure the elastic modulus. During the measurement, a sinusoidal wave force with a frequency of 1 Hz is applied to the bonding test piece, and the test atmosphere is heated. The heating rate is 5°C / min, and the temperature range is 25°C to 280°C. Then, the elastic modulus of the bonding test piece is measured relative to the temperature rise, and its inflection point is set as the glass transition temperature.
[0066] The bonding strength of the adhesive 50 after curing is more than 10MPa. The bonding strength of the adhesive 50 is measured as follows. First, a bisphenol F type resin 51, a curing agent 53, a curing accelerator 54, a dispersant 56, a silane coupling agent 55, and a magnetic powder 52 are mixed to obtain an adhesive 50 before curing. Then, the adhesive 50 is applied between two alumina substrates in a 5mm square. Therefore, in this measurement, the bonding strength in every 25 square millimeters can be measured. Then, by firing the two alumina substrates coated with the adhesive 50 before curing in an atmosphere of 150°C for 3 hours, a cured bonding test piece is prepared. Then, one alumina substrate and the other alumina substrate are respectively fixed to an autograph (model: AG XD Plus (manufactured by Shimadzu Corporation)) and a tensile test is performed. That is, in this embodiment, the tensile bonding strength is measured as the bonding strength. In the test, the tensile speed is 20mm / min. Then, the load at the time when the adhesive test piece was broken was defined as the adhesive strength of the adhesive 50. The test environment was set at a temperature of 23° C. and a relative humidity of 50%.
[0067] <Regarding the continuous printing properties of adhesive>
[0068] Four samples of adhesive 50 with different number average molecular weights of bisphenol F resin 51 were prepared, and the wire breaking time of each sample was measured. In the four samples, the conditions other than the number average molecular weight of bisphenol F resin 51 were the same. The volume ratio of magnetic powder 52 in the four samples was 35 vol%. It should be noted that the volume ratio here is the volume ratio of adhesive 50 before curing. The wire breaking time refers to the time from the time when the scraper is separated from the substrate after the adhesive 50 before curing is applied to the substrate using a scraper of a screen printer to the time when the adhesive 50 extending between the scraper and the substrate is broken. It should be noted that in the measurement of the wire breaking time, the conditions of the screen printer were set to a printing speed of 60 mm / s, a printing pressure of 0.2 MPa, a back pressure of 0.125 MPa, and a gap of 1 mm. Under this condition, the wire breaking time of the first, 25th, 50th, and 100th times of continuous printing was measured, and the average value was taken as the representative value of the wire breaking time.
[0069] The number average molecular weight of the bisphenol F type resin 51 in the first sample is the same as that in the above embodiment, which is 312 g / mol. The number average molecular weight of the bisphenol F type resin 51 in the second sample is 340 g / mol. The number average molecular weight of the bisphenol F type resin 51 in the third sample is 360 g / mol. The number average molecular weight of the bisphenol F type resin 51 in the fourth sample is 380 g / mol. These four samples are Examples 1, 2, 3 and Comparative Example 1 described in Table 1 below.
[0070] like Figure 4 As shown, the wire breaking time of the first sample is 11 seconds. The wire breaking time of the second sample is 12 seconds. The wire breaking time of the third sample is 20 seconds. The wire breaking time of the fourth sample is 80 seconds. In this way, it can be seen that the larger the number average molecular weight of the bisphenol F type resin 51 in the adhesive 50, the longer the wire breaking time. In addition, it can be seen that when the number average molecular weight of the bisphenol F type resin 51 exceeds 360g / mol, the wire breaking time becomes rapidly longer. That is, it can be seen that the inflection point of the wire breaking time relative to the increase of the number average molecular weight is about 360g / mol. It should be noted that when the adhesive 50 is applied using a screen printer, the longer the wire breaking time, the longer the standby time when the scraper is separated from the substrate, and the worse the continuous printing property. Therefore, from the perspective of the processing of the adhesive 50, it can be said that the number average molecular weight of the bisphenol F type resin 51 in the adhesive 50 is preferably less than 360g / mol.
[0071] In addition, five samples of adhesive 50 with different volume ratios of magnetic powder 52 were prepared, and the wire breaking time of each sample was measured. In the five samples, the conditions other than the volume ratio of magnetic powder 52 were the same. The number average molecular weight of bisphenol F type resin 51 in the five samples was 340g / mol. The definition of wire breaking time is the same as above. The volume ratio of magnetic powder 52 in the first sample was 20vol%. The volume ratio of magnetic powder 52 in the second sample was 25vol%. The volume ratio of magnetic powder 52 in the third sample was 30vol%. The volume ratio of magnetic powder 52 in the fourth sample was 35vol%. The volume ratio of magnetic powder 52 in the fifth sample was 40vol%. It should be noted that the volume ratio here is the volume ratio in the adhesive 50 before curing. These five samples are Examples 4, 5, 6, 2 and Comparative Example 2 described in Table 1 below.
[0072] like Figure 5 As shown, the wire breaking time of the first sample is 10 seconds. The wire breaking time of the second sample is 10 seconds. The wire breaking time of the third sample is 11 seconds. The wire breaking time of the fourth sample is 12 seconds. The wire breaking time of the fifth sample is 80 seconds. That is, it can be seen that in the adhesive 50, when the volume ratio of the magnetic powder 52 exceeds 35vol%, the wire breaking time becomes rapidly longer. That is, it can be seen that the inflection point of the increase in the wire breaking time relative to the volume ratio of the magnetic powder 52 is about 35vol%. Therefore, from the perspective of the processing of the adhesive 50, it can be said that the volume ratio of the magnetic powder 52 in the adhesive 50 is preferably less than 35vol%.
[0073] <About comparative testing>
[0074] Adhesives of Examples 1 to 9 and adhesives of Comparative Examples 1 and 2 shown in the following Tables 1 and 2 were prepared. Then, the adhesives of these Examples and the adhesives of Comparative Examples were tested for their properties before and after curing. It should be noted that in the adhesives of Examples 1 to 9 and the adhesives of Comparative Examples 1 and 2, the synthetic resin is bisphenol F type epoxy resin. In the adhesives of Examples 1 to 6 and the adhesives of Comparative Examples 1 and 2, the median particle size (D50) of the magnetic powder 52 is 0.8 μm. In addition, the adhesives of Examples 1 to 9 and the adhesives of Comparative Examples 1 and 2 contain magnetic powder 52, curing agent 53, curing accelerator 54, silane coupling agent 55, and dispersant 56, respectively.
[0075] <About Example 1 to Example 6>
[0076] Hereinafter, the results of comparative tests of the adhesives of Examples 1 to 6 and Comparative Examples 1 and 2 will be described.
[0077]
[0078] As shown in Table 1, in the adhesive of Example 1, the number average molecular weight of the bisphenol F type resin 51 is 312 g / mol. In the adhesive of Example 1, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 1, in the form before curing, the viscosity is 1833 Pa·s. In the adhesive of Example 1, in the form after curing, the magnetic permeability is 2.5. In the adhesive of Example 1, in the form after curing, the glass transition temperature is 125°C. In the adhesive of Example 1, in the form after curing, the bonding strength is 14 MPa.
[0079] It should be noted that the viscosity was measured using a rotational rheometer (model: MCR302 (manufactured by Anton Paar)). In the measurement using this device, a cone plate of Φ25 mm was used. In the measurement, the rotation mode was set to flow curve, and the shear rate was set to 0.01 s -1 It should be noted that the temperature of the test environment was 25°C.
[0080] In addition, the magnetic permeability is measured as follows. First, bisphenol F type resin 51, curing agent 53, curing accelerator 54, dispersant 56, silane coupling agent 55, and magnetic powder 52 are mixed to obtain an adhesive 50 before curing. Then, the adhesive 50 is fired in an atmosphere of 85°C for 1 hour to obtain a semi-cured adhesive 50. Then, the semi-cured adhesive 50 is filled in a mold with an outer diameter of Φ16 mm and an inner diameter of Φ10 mm, and a small hot press (model: H300-15 (manufactured by AS ONE)) is used. The pressurization condition is set to 4 MPa and the heating temperature is set to 150°C. The heating and pressurization are performed for 15 minutes to obtain a ring core. For the ring core, an impedance analyzer (model: E4991A (manufactured by Keysight Technologies) is used, and the condition is set to 10 MHz, and the measured real part magnetic permeability is measured as the magnetic permeability. It should be noted that the temperature of the test environment is 25°C.
[0081] In the adhesive of Example 2, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 2, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 2, the viscosity is 2528 Pa·s in the form before curing. In the adhesive of Example 2, the magnetic permeability is 2.5 in the form after curing. In the adhesive of Example 2, the glass transition temperature is 125° C. In the adhesive of Example 2, the bonding strength is 14 MPa in the form after curing.
[0082] In the adhesive of Example 3, the number average molecular weight of the bisphenol F type resin 51 is 360 g / mol. In the adhesive of Example 3, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 3, the viscosity is 3223 Pa·s in the form before curing. In the adhesive of Example 3, the magnetic permeability is 2.5 in the form after curing. In the adhesive of Example 3, the glass transition temperature is 125° C. In the adhesive of Example 3, the bonding strength is 14 MPa in the form after curing.
[0083] In the adhesive of Example 4, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 4, the volume ratio of the magnetic powder 52 is 20 vol%. In the adhesive of Example 4, the viscosity is 283 Pa·s in the form before curing. In the adhesive of Example 4, the magnetic permeability is 1.7 in the form after curing. In the adhesive of Example 4, the glass transition temperature is 125° C. In the adhesive of Example 4, the bonding strength is 14 MPa in the form after curing.
[0084] In the adhesive of Example 5, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 5, the volume ratio of the magnetic powder 52 is 25 vol%. In the adhesive of Example 5, the viscosity is 567 Pa·s in the form before curing. In the adhesive of Example 5, the magnetic permeability is 2.0 in the form after curing. In the adhesive of Example 5, the glass transition temperature is 125° C. In the adhesive of Example 5, the bonding strength is 14 MPa in the form after curing.
[0085] In the adhesive of Example 6, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 6, the volume ratio of the magnetic powder 52 is 30 vol%. In the adhesive of Example 6, the viscosity is 1143 Pa·s in the form before curing. In the adhesive of Example 5, the magnetic permeability is 2.2 in the form after curing. In the adhesive of Example 6, the glass transition temperature is 125° C. in the form after curing. In the adhesive of Example 6, the bonding strength is 14 MPa in the form after curing.
[0086] In the adhesive of Comparative Example 1, the number average molecular weight of the bisphenol F type resin 51 is 380 g / mol. In the adhesive of Comparative Example 1, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Comparative Example 1, the viscosity is 3760 Pa·s in the form before curing. In the adhesive of Comparative Example 1, the magnetic permeability is 2.5 in the form after curing. In the adhesive of Comparative Example 1, the glass transition temperature is 125° C. In the adhesive of Comparative Example 1, the bonding strength is 14 MPa in the form after curing.
[0087] In the adhesive of Comparative Example 2, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Comparative Example 2, the volume ratio of the magnetic powder 52 is 40 vol%. In the adhesive of Comparative Example 2, the viscosity is 4507 Pa·s in the form before curing. In the adhesive of Comparative Example 2, the magnetic permeability is 2.9 in the form after curing. In the adhesive of Comparative Example 2, the glass transition temperature is 125° C. In the adhesive of Comparative Example 2, the bonding strength is 14 MPa in the form after curing.
[0088] The results of the comparative test of the wire breaking time are that the wire breaking time of the adhesive of Example 1 is 11 seconds. The wire breaking time of the adhesive of Example 2 is 12 seconds. The wire breaking time of the adhesive of Example 3 is 20 seconds. The wire breaking time of the adhesive of Example 4 is 10 seconds. The wire breaking time of the adhesive of Example 5 is 10 seconds. The wire breaking time of the adhesive of Example 6 is 11 seconds. The wire breaking time of the adhesive of Comparative Example 1 is 80 seconds. The wire breaking time of the adhesive of Comparative Example 2 is 80 seconds.
[0089] In the "Judgment" column of "Characteristics (before curing)" in Tables 1 and 2, ○ indicates that the wire breakage time is less than 20 seconds. And × indicates that the wire breakage time is greater than 20 seconds. It should be noted that the above judgment value is determined as the limit of whether there is a risk that the adhesive 50 dripping from the scraper adheres to something other than the printed object.
[0090] According to the test results of Examples 1 to 6 and Comparative Example 1, when the number average molecular weight of the bisphenol F resin 51 is large, the tendency of the broken wire time to be longer is confirmed. That is, similar to the measurement results of the broken wire time using the above four samples, when the number average molecular weight of the bisphenol F resin 51 becomes greater than 360 g / mol, the increase ratio of the broken wire time becomes rapidly larger. In other words, it can be said that the number average molecular weight of the bisphenol F resin 51 is preferably 360 g / mol or less.
[0091] According to the test results of Examples 1 to 6 and Comparative Example 2, when the volume ratio of the magnetic powder 52 is large, the tendency of the wire breaking time to be longer is confirmed. That is, similar to the measurement results of the wire breaking time using the above five samples, when the volume ratio of the magnetic powder 52 exceeds 35 vol%, the increase ratio of the wire breaking time increases sharply. In other words, it can be said that the volume ratio of the magnetic powder 52 is preferably 35 vol% or less.
[0092] In addition, in the case of the adhesive with a viscosity of 3223 Pa·s in Example 3, the wire breaking time is 20 seconds. On the other hand, in the case of the adhesive with a viscosity of 3760 Pa·s in Comparative Example 1, the wire breaking time is 80 seconds. Therefore, it is predicted that the inflection point of the wire breaking time transition relative to the increase in viscosity is between 3223 Pa·s and 3760 Pa·s, that is, about 3500 Pa·s. Therefore, it can be said that the viscosity of the adhesive is preferably, for example, 3500 Pa·s or less.
[0093] It should be noted that the magnetic permeability of the adhesives of Examples 1 to 6 after curing exceeds 1.7. Thus, if the magnetic permeability exceeds 1.7, the adhesive 50 for bonding the drum-shaped core 10C and the top plate 10F of the coil component 10 can withstand practical use. That is, the adhesives of Examples 1 to 6 have a sufficient value of magnetic permeability as the adhesive 50 for the coil component 10.
[0094] <Examples 2, 3, 7 to 9>
[0095] Hereinafter, the results of comparative tests of the adhesives of Examples 2, 3, and 7 to 9 will be described.
[0096]
[0097] As shown in Table 2, the adhesive of Example 2 is the adhesive of Example 2. That is, in this adhesive, the median particle size (D50) of the magnetic powder 52 is 0.8 μm. In addition, the adhesive of Example 3 is the adhesive of Example 3. That is, in this adhesive, the median particle size (D50) of the magnetic powder 52 is 0.8 μm.
[0098] In the adhesive of Example 7, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 7, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 7, the median particle size (D50) of the magnetic powder 52 is 0.5 μm. In the adhesive of Example 7, the viscosity is 2911 Pa·s in the state before curing.
[0099] In the adhesive of Example 8, the number average molecular weight of the bisphenol F resin 51 is 360 g / mol. In the adhesive of Example 8, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 8, the median particle size (D50) of the magnetic powder 52 is 1.5 μm. In the adhesive of Example 8, the viscosity is 1820 Pa·s in the state before curing.
[0100] In the adhesive of Example 9, the number average molecular weight of the bisphenol F resin 51 is 340 g / mol. In the adhesive of Example 9, the volume ratio of the magnetic powder 52 is 25 vol%. In the adhesive of Example 9, the median particle size (D50) of the magnetic powder 52 is 2.5 μm. In the adhesive of Example 9, the viscosity is 1137 Pa·s in the state before curing.
[0101] The results of the comparative test of the wire breaking time showed that the wire breaking time of the adhesive of Example 7 was 16 seconds, the wire breaking time of the adhesive of Example 8 was 11 seconds, and the wire breaking time of the adhesive of Example 9 was 11 seconds.
[0102] According to the test results of Examples 2, 3, 7 to 9, if the median particle size (D50) of the magnetic powder 52 is in the range of 0.8 μm to 2.5 μm, the wire breaking time is 20 seconds or less. In addition, according to the test results, the smaller the median particle size (D50) of the magnetic powder 52 in the adhesive 50 is, the greater the viscosity tends to be. Therefore, it can be said that the median particle size (D50) of the magnetic powder 52 is preferably 0.8 μm or more.
[0103] <Effects of the present embodiment>
[0104] (1) According to the above embodiment, the adhesive 50 includes the magnetic powder 52, and thus has better magnetic permeability than the case where the magnetic powder 52 is not included. On the other hand, in the adhesive 50, the viscosity of the adhesive 50 tends to increase as the number average molecular weight of the bisphenol F type resin 51 increases. Here, the number average molecular weight of the bisphenol F type epoxy resin generally available on the market is known to be about 3300 g / mol and about 5500 g / mol, etc. On the other hand, the number average molecular weight of the bisphenol F type resin 51 in the above embodiment is 312 g / mol to 360 g / mol, which is significantly smaller than the number average molecular weight of the general bisphenol F type resin. By intentionally using the bisphenol F type resin 51 in such a number average molecular weight range, the viscosity of the adhesive 50 can be suppressed from increasing.
[0105] Similarly, the viscosity of the adhesive 50 tends to increase as the volume ratio of the magnetic powder 52 in the adhesive 50 increases. In the above embodiment, the volume ratio of the magnetic powder 52 in the adhesive 50 is 35 vol% or less. With such a volume ratio of the magnetic powder 52, the viscosity of the adhesive 50 can be suppressed from increasing.
[0106] As described above, according to the above-mentioned configurations, the magnetic permeability obtained as the magnetic permeability of the adhesive 50 for the coil component 10 is ensured, and the handling during manufacturing is simple. In particular, if the adhesive 50 of the above-mentioned embodiment is used, the wire breaking time can be suppressed when the adhesive 50 before curing is applied to the top plate 10F of the coil component 10 by a screen printer. That is, from the viewpoint of continuous printability, it is also a preferred adhesive 50.
[0107] (2) According to the above embodiment, the volume ratio of the magnetic powder 52 in the adhesive 50 is 20 vol% or more. With such a volume ratio of the magnetic powder 52, a preferred magnetic permeability is obtained in the adhesive 50 used for the coil component 10.
[0108] (3) According to the above embodiment, the adhesive 50 contains the silane coupling agent 55. According to this configuration, the bonding strength of the adhesive 50 can be improved. In particular, in the above embodiment, the adhesive 50 is interposed between the drum-shaped core 10C and the top plate 10F. The silane coupling agent 55 is useful for bonding with such an inorganic substance.
[0109] (4) According to the above embodiment, the adhesive 50 contains the dispersant 56. According to this configuration, the dispersant 56 can suppress the aggregation of the magnetic powder 52. Therefore, for example, even when the volume ratio of the magnetic powder 52 is large to a certain extent, the aggregation of the magnetic powder 52 can be suppressed.
[0110] (5) According to the above embodiment, the glass transition temperature of adhesive 50 is 125° C. or higher. That is, according to this configuration, the heat resistance of adhesive 50 is improved. Therefore, even when coil component 10 is used in a high temperature environment, for example, the reliability of coil component 10 can be suppressed from being reduced.
[0111] (6) In the above embodiment, the median particle size (D50) of the magnetic powder 52 is 0.8 μm or more. There is a tendency that the smaller the median particle size (D50) of the magnetic powder 52 in the adhesive 50 is, the greater the viscosity is. According to the results of the above comparative test, if the median particle size (D50) of the magnetic powder 52 is 0.8 μm or more, the wire breaking time of the adhesive 50 can be suppressed from being prolonged.
[0112] (7) In the above embodiment, the median particle size (D50) of the magnetic powder 52 is 2.5 μm or less. The larger the median particle size (D50) of the magnetic powder 52, the more likely it is that the magnetic powder 52 will collide with each other in the adhesive 50. That is, depending on the shape of the area where the adhesive 50 is applied, there is a risk that the magnetic powder 52 will not follow the shape of the applied area but will be concentrated in the adhesive 50. If the median particle size (D50) of the magnetic powder 52 is within the above range, these problems are less likely to occur.
[0113] (8) In the above embodiment, the bonding strength of the adhesive 50 to alumina per 25 mm2 is 10 MPa or more. By using the adhesive 50 having such a bonding strength, a preferable bonding strength can be obtained in the coil component 10 as well.
[0114] (9) In the above embodiment, the coil component 10 has a closed magnetic circuit formed by the flange portion 20 and the top plate 10F. Thus, as the adhesive 50 for bonding the flange portion 20 and the top plate 10F constituting the closed magnetic circuit, the adhesive 50 of the above embodiment is particularly preferred in terms of improving the overall characteristics of the coil component 10.
[0115] <Change Example>
[0116] The above-described embodiment and the following modified examples can be implemented in combination with each other within the scope of no technical contradiction.
[0117] <About changes related to coil components>
[0118] The shape of the winding core 11 is not limited to the example of the above-mentioned embodiment. For example, the shape of the winding core 11 may be a cylindrical shape, or a polygonal column shape other than a quadrangular column shape.
[0119] The configuration of the drum-shaped core 10C is not limited to the above-described embodiment. For example, the drum-shaped core 10C may not include the first recess 21A and the second recess 22A. In this case, for example, the first electrode 31 and the second electrode 32 may be separated from each other, and the third electrode 33 and the fourth electrode 34 may be separated from each other.
[0120] The material and shape of the external electrode 30 are not limited to the examples in the above embodiment. For example, the material of the plating layer in the external electrode 30 may also be an alloy of tin and nickel. In addition, the external electrode 30 may not have a plating layer. In this case, the portion where the conductive metal layer is exposed can be used as the external electrode 30.
[0121] The coil component 10 may include at least one wire. When the number of the wire is one, one external electrode 30 may be provided on the first flange portion 21 and one external electrode 30 may be provided on the second flange portion 22 .
[0122] The coil component 10 is not limited to the configuration including the drum-shaped core 10C and the top plate 10F. The coil component 10 only needs to include a first core around which a wire is wound and a second core connected to the first core via the adhesive 50. The first core and the second core may be bonded together using the adhesive 50.
[0123] <About changes related to adhesives>
[0124] The adhesive 50 is not limited to being applied to the coil component 10. The adhesive 50 is preferably applied to an electronic component having a core made of a magnetic material.
[0125] The type of the curing agent 53 in the adhesive 50 is not limited to the example of the above embodiment. A curing agent corresponding to the bisphenol F type resin 51 can be used.
[0126] The volume ratio of the magnetic powder 52 in the adhesive 50 may be 35 vol% or less. That is, the volume ratio of the magnetic powder 52 in the adhesive 50 may be less than 20 vol%. The volume ratio of the magnetic powder 52 may be set so that a preferred magnetic permeability can be obtained in the coil component 10 used.
[0127] The number average molecular weight of the bisphenol F type resin 51 in the adhesive 50 may be in the range of 312 g / mol to 360 g / mol.
[0128] The adhesive 50 may contain a silane coupling agent 55, a dispersant 56, and a curing accelerator 54. In addition, the types of the silane coupling agent 55, the dispersant 56, and the curing accelerator 54 are not limited to the examples of the above-mentioned embodiment.
[0129] The glass transition temperature of the cured adhesive 50 may be lower than 125° C. The glass transition temperature may be a preferred glass transition temperature depending on the intended use of the adhesive 50 .
[0130] The median particle size (D50) of the magnetic powder 52 in the adhesive 50 may be less than 0.8 μm or greater than 2.5 μm. The median particle size (D50) of the magnetic powder 52 may be a value that is preferable in the handling of the adhesive 50 .
[0131] After curing, the bonding strength of the adhesive 50 to the alumina per 25 square millimeters may be less than 10 MPa. The bonding strength of the adhesive 50 is preferably within a range that allows the top plate 10F and the drum-shaped core 10C to be sufficiently bonded.
[0132] <Note>
[0133] The following describes technical ideas that can be derived from the above-mentioned embodiments and modified examples.
[0134] [1] An adhesive comprising a bisphenol F resin, a curing agent for the bisphenol F resin, and magnetic powder, wherein the volume ratio of the magnetic powder to the adhesive is 35 vol% or less, and the number average molecular weight of the bisphenol F resin is 312 g / mol to 360 g / mol.
[0135] [2] The adhesive according to [1], wherein the volume ratio of the magnetic powder in the adhesive is 20 vol% or more.
[0136] [3] The adhesive according to [1] or [2], further comprising a silane coupling agent.
[0137] [4] The adhesive according to any one of [1] to [3], further comprising a dispersant for dispersing the magnetic powder.
[0138] [5] The adhesive according to any one of [1] to [4], wherein the median particle size (D50) of the magnetic powder is 0.8 μm or more.
[0139] [6] The adhesive according to any one of [1] to [5], wherein the median particle size (D50) of the magnetic powder is 2.5 μm or less.
[0140] [7] The adhesive according to any one of [1] to [6], wherein the glass transition temperature after curing is 125° C. or higher.
[0141] [8] The adhesive according to any one of [1] to [7], wherein after curing, the adhesive has a bonding strength to alumina of 10 MPa or more per 25 mm2.
Claims
1. An adhesive comprising a bisphenol F resin, a curing agent for the bisphenol F resin and magnetic powder, The volume ratio of the magnetic powder to the adhesive is 35 vol% or less, The number average molecular weight of the bisphenol F resin is 312 g / mol to 360 g / mol. 2 . The adhesive according to claim 1 , wherein the volume ratio of the magnetic powder in the adhesive is 20 vol % or more.
3. The adhesive according to claim 1, wherein It further contains a silane coupling agent.
4. The adhesive according to claim 1, wherein The invention further contains a dispersant for dispersing the magnetic powder.
5. The adhesive according to claim 1, wherein The median particle size of the magnetic powder, ie, D50, is greater than 0.8 μm.
6. The adhesive according to claim 1, wherein The median particle size of the magnetic powder, ie, D50, is less than 2.5 μm. 7 . The adhesive according to claim 1 , which has a glass transition temperature of 125° C. or higher after being cured. 8 . The adhesive according to claim 1 , wherein after curing, the adhesive has a bonding strength to alumina of 10 MPa or more per 25 square millimeters.
Citation Information
Patent Citations
Common mode choke coil and manufacturing method thereof
JP2021190633A